PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN SEPATU BATA PADA TOKO SEPATU DI KABUPATEN JEMBER - Pratama, Ahmad Febrian; Setyowati, Trias; Hermawan, Haris (Fakultas Ekonomi dan Bisnis, 2023)
Very tight market competition requires companies to be able to adapt to consumer needs in order to be able to compete in the market. A decrease in sales can be used as an indicator of a problem that must be considered by the company, because in this case the sales result is the main income for the company to continue its business. The purpose of this research is to examine and identify the effect of marketing mix on consumer purchasing decisions at shoe stores in Jember Regency. This research was conducted by distributing questionnaires to 125 consumer respondents who had purchased shoes at the Bata Shoe store in Jember Regency. The data that has been collected was analyzed using multiple linear regression tests using the SPSS application. The results of multiple regression analysis show that the variables product, price, promotion, place, people and process have a positive relationship with the regression coefficient on purchasing decisions and variable physical evidence has a negative relationship with the regression coefficient on purchasing decisions, while the results of the t test show that product, price, people and process have a significant effect on purchasing decisions of 0.000 and variable promotion, place and physical evidence have no significant effect on purchasing decisions of 0.074, 0.398, 0.495. The results of the study show that the marketing mix includes product, price, place, promotion, people, physical evidence and process simultaneously have a significant influence on decisions purchase of shoes at the Bata Shoes store in Jember Regency.